Benjamin Disraeli letters. - Disraeli, Benjamin, 1804-1881 (CEL - Canadian Publishers Collection., 1989)
Part of the critically acclaimed Letters of Benjamin Disraeli series. This volume contains or describes letters written by Disraeli between 1842 and 1847.